Utilization of Social Media in a Digital Marketing Strategy for Cassava Chips Products to Improving Students' Entrepreneurial Spirit - Hanifa Nurahmi; Haryadi Adhan; Mu'hamad Asfi Romdon; Tri Yulistia; Eko Risdianto (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
The purpose of this research is to increase the entrepreneurial spirit of students by utilizing social media in marketing strategies for Cassava Chips products. This study uses qualitative research methods with data collection techniques, namely observation, interviews, documentation, and questionnaires. This research was conducted on March 21, 2023, at Bengkulu University. The population and samples taken from this study were physics education students class of 2020. For the population, there were 51 students, while the samples were taken, namely 10 physics education students class of 2020. Observations were made when making observations while the questionnaire contained responses to Cassava Chips products. carried out by students as respondents. The results of this study indicate that the consumed cassava chips are very good and worth selling. The results of the study also stated that utilizing social media in marketing cassava chip products could improve the entrepreneurial spirit of Physics Education students for the better.